State and events for Web services: a comparison of five WS-resource framework and WS-notification implementations - Humphrey, M.; Meder, S.; Pickles, S.; Mc Keown, M.; Wasson, G.; Jackson, K.; Boverhof, J.; Rodriguez, M.; Gawor, J.; Bester, J.; Lang, S.; Foster, I. (HPDC-14. Proceedings. 14th IEEE International Symposium on High Performance Distributed Computing, 2005, 2005)
The Web services resource framework defines conventions for managing state in distributed systems based on Web services, and WS-notification defines topic-based publish/subscribe mechanisms. We analyze five independent and quite different implementations of these specifications from the perspectives of architecture, functionality, standards compliance, performance, and interoperability. We identify both commonalities among the different systems (e.g., similar dispatching and SOAP processing mechanisms) and differences (e.g., security, programming models, and performance). Our results provide insights into effective implementation approaches. Our results may also provide application developers, system architects, and deployers with guidance in identifying the right implementation for their requirements and in determining how best to use that implementation and what to expect with regard to performance and interoperability.